2016
DOI: 10.1111/jdi.12458
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and physical activity of adult patients with type 2 diabetes in Zhejiang province of eastern China: Data from a cross‐sectional study

Abstract: Aims/IntroductionLifestyle management helps improve the clinical outcome of patients with type 2 diabetes. The present study aimed to obtain lifestyle data on the dietary and physical activity of adult type 2 diabetes patients in Zhejiang province of eastern China for better patient education and improvement of clinical management.Materials and MethodsA cross‐sectional survey of 607 adult type 2 diabetes patients was carried out in 12 hospitals within eight cities of Zhejiang province. Data were collected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(41 reference statements)
0
6
1
Order By: Relevance
“…A cross-sectional survey by He et al [17] indicates that nearly 50% of diabetes subjects didn't meet minimum PA recommendations, whereas the number raised to almost 60% in our study. He's survey was carried out in 12 hospitals and targeted outpatient populations with higher attention to lifestyle interventions compared to community-dwelling participants, which may partly explain the numerical discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
“…A cross-sectional survey by He et al [17] indicates that nearly 50% of diabetes subjects didn't meet minimum PA recommendations, whereas the number raised to almost 60% in our study. He's survey was carried out in 12 hospitals and targeted outpatient populations with higher attention to lifestyle interventions compared to community-dwelling participants, which may partly explain the numerical discrepancy.…”
Section: Discussioncontrasting
confidence: 83%
“…The difference was statistically significant, as was the percentage of energy from individual macronutrients. In the group of women, the percentage of energy from carbohydrates and protein was higher, and the percentage of energy from fat was lower in daily food intake [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean study, the distribution of macronutrients (C:F:P, % of total energy) was reported as 68%:16%:16%, respectively [ 29 ]. According to data from eastern China, in patients with T2DM, the proportion of calories derived from carbohydrate, fat and protein were 61.4%, 25.4% and 13.3%, respectively [ 30 ]. As we can see from the Asian data, an HCLF pattern (C:F:P = 60%:16%–25%:15%–24%) is predominant in Asian patients with T2DM.…”
Section: Literature About the Effects Of High Carbohydrate On Metamentioning
confidence: 99%